2022
DOI: 10.1002/lsm.23615
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a 755‐nm picosecond laser and hydroquinone 2% cream versus hydroquinone 2% cream alone for the treatment of melasma: A randomized, split‐face, and controlled trial

Abstract: Background While combined laser and topical treatments are currently a common approach to melasma treatment, data on the efficacy and safety of this combined therapy remain scarce, with studies showing varied results. Objective To compare the efficacy and safety of hydroquinone (HQ) cream alone versus HQ cream combined with 755‐nm picosecond (PS) laser in the treatment of melasma. Method Twenty subjects presenting with mixed‐type melasma were enrolled in the study. All patients were instructed to apply 2% HQ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Our results were consistent with those described in other studies which also confirmed the efficacy of PSNYL ( 11 , 14 17 ) and PSAL ( 5 , 8 10 , 18 20 ) for melasma. However, only two ( 14 , 21 ) and three ( 5 , 9 , 22 ) of the studies were RCTs regarding non-fractional PSNYL and PSAL, respectively. This randomized controlled study aimed to provide reliable evidence-based interventions for the clinical treatment of melasma using Picos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were consistent with those described in other studies which also confirmed the efficacy of PSNYL ( 11 , 14 17 ) and PSAL ( 5 , 8 10 , 18 20 ) for melasma. However, only two ( 14 , 21 ) and three ( 5 , 9 , 22 ) of the studies were RCTs regarding non-fractional PSNYL and PSAL, respectively. This randomized controlled study aimed to provide reliable evidence-based interventions for the clinical treatment of melasma using Picos.…”
Section: Discussionmentioning
confidence: 99%
“…However, mMASI or hemi-MASI displayed an increasing trend in the later stages of follow-up in the two studies mentioned above ( 21 , 31 ), suggesting a likelihood of melasma recurrence after a period of cessation of treatment. Moreover, a recent split-face study suggested that there was not a substantial advantage in the PSAL and 2% HQ combination therapy versus the 2% HQ monotherapy ( 22 ). Thus, whether combination therapy has benefits and in what specific domains, such as enhancing the therapeutic effect or extending the duration of the therapeutic outcome, are problems that still require scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Since melanin has a very broad absorption spectrum, extending from ultraviolet wavelengths well into the infrared spectrum, a variety of lasers and light sources have been used to treat melasma. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Q-switched lasers and fractionated thulium lasers are commonly used to treat melasma, due to their ability to target pigmentation while minimizing subsequent inflammation. [7][8][9][11][12][13][15][16][17][18] The relatively recent development of picosecond-domain lasers enables the delivery of high peak powers with relatively low fluences, minimizing inflammation while still targeting melanin pigment.…”
Section: Introductionmentioning
confidence: 99%
“…Since melasma is often exacerbated by inflammation, picosecond-domain laser treatments that limit inflammation while targeting melanin pigment may be ideal for treating melasma. 10,14,[19][20][21] In the current study, we investigate the effect of treatment with a 1064-nm picosecond-domain laser, delivering highly focused, fractionated laser energy in an array of 101, 10 × 10 beamlets via a holographic optic, on improving the appearance of melasma. Since melasma is highly affected by sun-exposure and waxes and wanes throughout the course of a year, the pretreatment and final post-treatment digital images were taken exactly 1-year apart.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation